Analysis of Law Number 23 of 2004 Concerning The Eliminator of Domestic Violence In Indonesia - Ahmat Sahrudi; Abdul Parid Asari; Syahrul Anwar; Claire Lajaunie; Naimah Mohamad Nasir (Yayasan Cendekia Gagayunan Indonesia, 2026)
The phenomenon of domestic violence (KDRT) in Indonesia is a serious problem that is not only in the private sphere, but also reflects human rights violations and criminal acts. This study aims to analyze the position, substance, and implementation of Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT Law) in the national legal system. The method used is normative juridical research with legislative, conceptual, and court decision analysis approaches as the main study material. The results of the study show that the PKDRT Law has a strategic role in expanding the definition of domestic violence, including physical, psychological, sexual, and neglectful violence. In addition, this law provides comprehensive victim protection instruments, such as protection orders, legal assistance, and recovery services. Analysis of court decisions indicates that judges have consistently used the PKDRT Law as a basis for legal considerations, although there are variations in the juridical and sociological approaches used in deciding cases. However, the implementation of the PKDRT Law still faces various challenges, such as a strong patriarchal culture, social stigma against victims, and limited access to legal services and protection. Therefore, it is necessary to strengthen synergy between law enforcement agencies, increase public awareness, and optimize victim protection services to ensure the effectiveness of the implementation of the PKDRT Law in ensuring justice and protection for victims of domestic violence.